Synthesis and Characterization of New vic-Dioximes with Benzo-15-crown-5 Derivatives and Their Nickel(II), Copper(II), Cobalt(II) Complexes - Battaloglu, Rifat; Ihsan Pekacar, A.; Kemal Yildiz, Y. (Asian Journal of Chemistry, 2012)
Benzo-15-crown-5-p-toluidino-glyoxime (1) and N(1-naphthyl)amino-benzo-15-crown-5- glyoxime (2) were synthesized by classical methods. Their structures were confirmed by spectral techniques. Both of them were capable of forming complexes with various metal ions (Co2+, Cu2+ and Ni2+). The structure of the complexes was confirmed by FT-IR, mass spectra and elemental analyses.